Responses of intertidal macroalgae and associated fauna to interactive processes acting over multiple spatial scales,For App - Mostert, Bruce Petrus (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
The decrease of biological diversity from low latitudes near the equator towards high latitudes is one of the most fundamental patterns noted in ecology. These trends have been the subject of numerous terrestrial and marine studies and have caused the proposal of several explanatory hypotheses. No single hypothesis has adequately accounted for these observed trends. Furthermore, large-scale patterns are frequently modified by processes acting at meso- to small-scales. It is imperative to understand the interaction of these processes to elucidate the mechanisms controlling the structure of intertidal assemblages. The main aim of this thesis was to test the influence of multiple processes at a range of spatial scales on biogenic engineers. Biogenic engineers, such as macroalgae, have been reported to be strongly influenced by processes such as grazing, biogeography and upwelling and subsequent effects are expected to be linked to their associated assemblages. I used infaunal assemblages associated with macroalgae as a model system to understand the interactive effects of meso-scale upwelling in conjunction with large-scale factors (regional and biogeographic). Three species of macroalgae, Hypnea spicifera, Champia lumbricalis and Bifurcaria brassicaeformis, inhabiting different but overlapping home ranges were used in this study. Smaller scale, physical attributes and the associated fauna of these algal species were compared. The effects of meso- to large-scale physical gradients on marine organisms have been investigated in many instances and resultant gradients in physical variables observed. This study was undertaken to investigate morphological trends exhibited by Hypnea spicifera and Champia lumbricalis to compare possible similarities between coastlines and to determine if inferred meso- to large-scale processes influence physical trends in a similar manner despite the coastlines being affected by different hydrodynamic processes. The macroalgae were located in two distinctly different upwelling regimes, Hypnea spicifera on the east and south coasts and Champia lumbricalis on the west coast. Upwelling (delivery of nutrients and primary production) was not found to be an important factor in determining the physical characteristics of macroalgae but there were clear patterns linked to latitude. Mean percentage cover of Hypnea spicifera was positively correlated with distance along the east and south coasts. Mean mass and mean surface area of H. spicifera were, however, negatively correlated with distance from Port St Johns. Mean frond length showed a negative trend but this relationship was not statistically significant. On the west coast, there was a significant increase in mean frond length from north to south for Champia lumbricalis. Mean surface area and mean mass of C. lumbricalis exhibited non-significant negative trends from north to south while there was a non-significant positive trend for mean percentage cover. Following the "Productivity Hypothesis" , these patterns from north to south along the coastlines of South Africa could have important implications for biodiversity associated with these algae. Many previous studies have focussed on the effects of upwelling on species (i.e. effects of nutrients and temperature) but have failed to separate this effect from large scale effects such as biogeography and latitudinal gradients. I tested the influence meso-scale upwelling, large-scale biogeographic processes and latitudinal gradients with two different species of macroalgae one on the east and south coasts of South Africa and the other on the west coast. Hypnea spicifera inhabits the east and south coasts of South Africa spanning two biogeographic provinces and is generally affected by relatively weak upwelling, whereas Champia lumbricalis inhabits the west coast spanning one biogeographic province which is subjected to intense persistent upwelling year round. Within the east and west coast biogeographic provinces there are, however, regions with both upwelling and non-upwelling. On the east and south coasts, entire assemblages differed significantly among the three Regions (St Lucia, Port Alfred and Knysna, while assemblages between upwelling/non-upwelling areas were not different. Assemblages on the different shores differed significantly from each other. There were no significant effects of region or upwelling for the number of individuals of Crustacea or Polychaeta, while Mollusca showed a significant effect of region. The number of individuals of other taxa showed a significant interaction of region and upwelling. Region had a significant effect on number of species of molluscs and other taxa, while there was no effect for either region or upwelling for the Crustacea or Polychaeta. In general different factors were shown to be important (region and shore) while upwelling was rarely important. On the west coast assemblages associated with C. lumbricalis were not influenced by region or upwelling but there were significant differences between shores. Region, upwelling ad shore did not affect number of individuals. There was a significant interaction of region and upwelling for the number of species of crustaceans, while numbers of species of Mollusca, Polychaeta and other taxa showed no effects. In general, regional factors strongly influenced most organisms, while upwelling played a minor role. Hypotheses about differences between upwelling and non-upwelling regions in terms of species abundances and composition due to the input of cold nutrient rich water were not supported. A link between the effects of larger-scale biogeographic factors and their influence on habitat forming taxa and the resultant effects on associated infauna would be a likely explanation for the patterns observed in this study. Diversity of assemblages is known to be influenced by the structural complexity of a habitat, increasing complexity increases the amount of available niches therefore potentially increasing the number of species found within that habitat. Three species of macroalgae, Hypnea spicifera, Champia lumbricalis and Bifurcaria brassicaeformis were selected on the basis of being structurally similar and having their distributional ranges overlap in order to elucidate the effects of structure and macroalgal species on associated assemblages. Hypnea spicifera is different in terms of surface area and biomass from Champia lumbricalis and Bifurcaria brassicaeformis. Assemblages of species found on the three rhodophytes showed both shore and the species of alga had significant effects on composition. Only numbers of individuals of molluscs were affected by the species of alga. Crustacea and Polychaeta showed an interaction of the species of alga with shore. In the case of this study, it is likely that the three species of macroalgae mitigate biological stressors such as predation and physical stressors such as wave exposure and desiccation. In general, meso-scale upwelling is suggested to be marginalised when considering the structuring of assemblages associated with macroalgae, while large scale biogeography has more of an influence. Within shores, assemblages were also strongly influenced by smaller-scale factors such as differences in the structure and species of alga. This study indicates the importance of investigating patterns across a range of spatial scales to gain a comprehensive understanding of factors influencing intertidal organisms.
Keywords: Biodiversity -- South Africa; Spatial ecology; Marine algae -- South Africa; Marine organisms -- Effect of water pollution on